Kajian Penerapan Teknologi Informatika pada Dunia Kesehatan - Putra, Rafi Septiawan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The purpose of this research is to study the application of information technology to the world of health. Research methods This research uses qualitative approaches and library methods, both involving collection of library data through reading, recording, and processing research materials. Telenursing results actually make it much easier to access health care for under-serviced populations, like monitoring services at home or individuals with chronic health problems. However, this technology is still not optimally used in Indonesia. After reading the description above, it can be concluded that, in cases where patients are unlikely to obtain health services or nursing directly, either for remote reasons or because they want to save and efficiently save their time during the trip, the telenursing service is one of the options that can be used.